Mechanical characterization of femoral popliteal artery: experiments, histology, and model comparison - Renye Cai; Aoling Liu; Qingkun Hu; Jie Lu; Heng Zhang; Chunyu Kong; Yiwei Zhu; Xiaolong Gu; Xuwen Lai; Zhi-Qiang Feng; François Peyraut (Materials & Design)
Peripheral artery disease (PAD) has a high mortality rate and can bring various cardiovascular disease risks, making it an extremely serious type of disease. The porcine femoral popliteal artery (FPA) was selected as research objects to obtain detailed mechanical behavior and arterial structure information of lower limb arteries through biaxial tensile experiments and histopathological analysis. The results showed that the FPA exhibits higher compliance in the longitudinal direction than in the circumferential direction and greater stiffness in the circumferential direction. Histopathological analysis revealed the microstructural changes in the arterial samples after stretching, including partial rupture of elastic fibers, rearrangement and distribution of collagen fibers, and morphological changes in smooth muscle cells (SMCs). The experiment found that tissue damage begins to accumulate when FPA strain exceeds 30%. Both the polyconvex quadratic polynomial SEF (Strain Energy Function) and the exponential SEF effectively captured the mechanical response of these arteries. This study advances the understanding of the mechanical properties and injury mechanisms of the FPA, evaluates the applicability of SEFs, and provides a foundation for future computer modeling research.